The role of vocational training in addressing skilled labor shortages - Langen, Henrika [Verfasser] (My University, 2025)
“This study examines how regional and occupation-specific skilled labor shortages influence companies' involvement in apprenticeship training. It explores the relationship between skilled labor shortages and demand for apprentices, qualification requirements, new apprenticeship contracts, and premature contract terminations in Germany. Skilled labor shortages are measured using the ratio of unemployed skilled jobseekers to job vacancies and a skilled labor shortage indicator from the Federal Employment Agency. Involvement in apprenticeship training is measured using annual apprenticeship contract data. To estimate the relationship between skilled labor shortages and apprenticeship activities, the study uses a two-way fixed effects model and a robust difference-in-differences approach. The findings show that skilled labor shortages bring about higher demand for apprentices and more hires, with companies recruiting a larger share of apprentices with lower qualifications. However, the impact on premature contract terminations remains unclear. Additionally, the study reveals significant variation across occupations in how companies adjust apprenticeship practices.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 3.2 Unternehmen und Behörden; G 1.3.1.1 Ausbildungsstellenmarkt; 370; Fachkräftemangel; Einflussfaktor; Ausbildungsverhalten; Ausbildungsplatznachfrage; Qualifikationsanforderung; Ausbildungsabbruch